NITROGÊNIO E Azospirillum brasilense NO DESENVOLVIMENTO INICIAL DA CANA-DE-AÇÚCAR (Colloquium Agrariae. ISSN: 1809-8215, 2020)
The use of plant growth promoting bacteria and nitrogen fertilization can improve the growth and development of sugarcane plants due to improved nitrogen acquisition by plants. This study was carried out to evaluate the effects of the interaction between inoculation of Azospirillum brasilense and the application of N on the initial growth of sugarcane plants (Saccharum spp.). Twenty-day-old plants from 3.0 cm long mini-stems of the RB 86-7515 sugarcane variety, produced in plastic trays containing commercial substrate were used. The plants were transplanted to 12 L plastic pots. The experimental design was a randomized block design, arranged in a 2 × 5 factorial scheme, with four replications. The treatments were constituted by inoculation or not of seedlings with Azospirillum brasilense and the application of five nitrogen rates (0, 30, 60, 90 and 120 mg dm–3 of N). At 60 days after plant transplantation, leaf number (NF), number of tillers (NP), plant height (AP), stem diameter (DC), shoot dry matter yield (MSPA) were evaluated. and from the roots (MSR). The results showed that the application of Azospirillum brasilense inoculant during the initial phase of plant growth has a beneficial effect on sugarcane development only when associated with high doses of nitrogen in cover. In the absence of nitrogen fertilization, sugarcane variety RB 86-7515 has negative response to plant inoculation with Azospirillum brasilense.